Boosting hydrogen production with ultralow working voltage by selenium vacancy‐enhanced ultrafine platinum–nickel nanowires. Issue 1 (20th January 2022) - Jin, Yu; Zhang, Zhe; Yang, Hao; Wang, Pengtang; Shen, Chenqi; Cheng, Tao; Huang, Xiaoqing; Shao, Qi
Abstract: Defect engineering provides a highly potential way to yield exceptional catalytic performance. Herein, we first report the selenium (Se) vacancies‐decorated ultrafine platinum–nickel (PtNi‐Sev ) nanowires, as a bifunctional catalyst for the hydrogen evolution reaction (HER) and methanol oxidation reaction (MOR). The optimized PtNi‐Sev exhibits obvious enhancement for HER and MOR compared to PtNi nanowires. It displays merely an overpotential of 18.8 mV for alkaline HER and the outstanding MOR performance (3.51 A/mgPt ). When applying in one symmetric overall water splitting electrolyzer coupling with HER and MOR, an ultralow working voltage of 0.637 V with 100% Faraday efficiency for hydrogen production was achieved at the current density of 10 mA/cm 2 . Further investigations reveal that the weakened hydrogen binding energy, strong OH binding as well as relative weak CO binding are responsible for the improved HER and MOR activities. Abstract : Selenium vacancies‐decorated ultrafine PtNi nanowires have been successfully created as efficient catalysts for the symmetric overall water splitting electrolyzer coupling with hydrogen evolution reaction and methanol oxidation reaction, achieving an ultralow working potential of 0.637 V and 100% Faraday efficiency of hydrogen production at 10 mA/cm 2 .